"I'm just too busy to exercise": Reframing the negative thoughts associated with exercise-related cognitive errors. (July 2019) - Locke, Sean R.; McKay, Rhyann C.; Jung, Mary E.
Abstract: Objectives: Exercise-related cognitive errors (ECEs) represent a negative lens that distorts individuals' view of exercise. Such thinking can inhibit individuals' behaviour change efforts. Reframing is an evidence-based counselling strategy used to help individuals evaluate the evidence for and against their biased thoughts. Reframing is commonly used within the clinical counselling domain, however, there is no systematic evidence base for its use in an exercise setting for a sample of non-clinical individuals. Two proof-of-concept studies examined whether reframing could attenuate ECEs in the exercise context. Design: Study 1 ( N  = 22) used a one-group pre-post design to examine cognitive error reframing (REF) in a sample of university staff and students. Study 2 ( N  = 28) used a randomized design (REF vs. attention control [AC]) to examine ECEs and exercise changes in a sample of individuals with prediabetes. Methods: Those receiving REF were prompted to identify, challenge, and reframe their negative exercise thoughts. Results: Both studies demonstrated ECE reductions following reframing. Changes in self-regulatory social cognitions were observed in Study 1. Those receiving REF in Study 2 reported greater increases in their self-reported exercise four weeks following the diabetes program compared to those in AC. Conclusions: REF may help individuals to reduce their biased exercise thoughts when making behaviour change efforts. While findings should be viewed as preliminary given the early research stage and sample sizes, we hope they spark future reframing research within the exercise context. Highlights: Reframing was shown to reduce biased thoughts about exercise. Reframing was shown to reduce decisional struggle and increase exercise intentions. Those receiving reframing were more active one month later compared to control.